2015
DOI: 10.1039/c5ay01809a
|View full text |Cite
|
Sign up to set email alerts
|

An eco-friendly HPTLC method for assay of eszopiclone in pharmaceutical preparation: investigation of its water-induced degradation kinetics

Abstract: An eco-friendly, sensitive and selective high-performance thin-layer chromatographic method was developed and validated for analysis of eszopiclone in bulk powder and formulation. The method employed HPTLC aluminium plates precoated with silica gel 60F-254 as the stationary phase. The solvent system consisted methanol-water (6: 4, v/v). Densitometric analysis of eszopiclone was carried out at 300 nm. This system was found to give compact spot for eszopiclone (R f value of 0.48 ± 0.02). The proposed method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Their values were found to surpass 0.9990, a good indication of the peaks' homogeneity as well as the absence of any masked co-eluting components. 47,48 Moreover, the similar identity of the standard and sample of each drug was guaranteed through the good correlation and superimposition of their UV spectra, as illustrated in Fig. 3A and B.…”
Section: Resultsmentioning
confidence: 74%
“…Their values were found to surpass 0.9990, a good indication of the peaks' homogeneity as well as the absence of any masked co-eluting components. 47,48 Moreover, the similar identity of the standard and sample of each drug was guaranteed through the good correlation and superimposition of their UV spectra, as illustrated in Fig. 3A and B.…”
Section: Resultsmentioning
confidence: 74%
“…Chromatographic analysis offers many advantages for the analysis of various compounds. 13–27 Thus, our proposed RP-HPLC method shows many advantages over the reported ones. It shows higher selectivity and sensitivity.…”
Section: Resultsmentioning
confidence: 94%
“…In this work, two novel comprehensive approaches were applied for evaluating the greenness of the applied analytical methodology; GAPI and analytical Eco-scale [53][54][55]. These approaches compare different parameters and different steps of our developed analytical method to those applied in previous reports including; HPLC [16], HPTLC [23] and spectrophotometric [7] methods.…”
Section: Assessment Of Methods Greennessmentioning
confidence: 99%
“…Few methods have been reported for the determination of EZP pharmaceutical dosage forms in literature. Pandya et al [7] has reported a simple spectrophotometric method by direct measurement of maximum absorbance of EZP peak at 305 nm, El-Yazbi et al [23] has reported a HPTLC method for EZP determination using methanolwater (6 : 4, v/v) as a mobile phase. While a HPLC method was reported by Ravi et al [16] with a mobile phase consisting of phosphate buffer of pH, 3.5 and acetonitrile in the ratio of 50 : 50 (v/v).…”
Section: Comparison To Other Reported Methodsmentioning
confidence: 99%
See 1 more Smart Citation